Integrated cmos rectifier for rf-powered wireless sensor network nodes - Mohammed Abdul Raheem Esmail Alselwi; Yan Chiew Wong; Zul Atfyi Fauzan Mohammed Napiah (Institute of Advanced Engineering and Science, 2019)
This article presents a review of the CMOS rectifier for radio frequency energy harvesting application. The on-chip rectifier converts the ambient low-power radio frequency signal coming to antenna to useable DC voltage that recharges energy to wireless sensor network (WSN) nodes and radiofrequency identification (RFID) tags, therefore the rectifier is the most important part of the radio frequency energy harvesting system. The impedance matching network maximizes power transfer from antenna to rectifier. The design and comparison between the simulation results of one- and multi-stage differential drive cross connected rectifier (DDCCR) at the operating frequencies of 2.44GHz, and 28GHz show the output voltage of the multi-stage rectifier doubles at each added stage and power conversion efficiency (PCE) of rectifier at 2.44GHz was higher than 28GHz. The (DDCCR) rectifier is the most efficient rectifier topology to date and is used widely for passive WSN nodes and RFID tags.